Methods for monitoring juvenile fish in variable coastal habitats : the effect of a bridge construction on gadoid numbers in Mjóifjörður, Iceland - Leu, Traian C. (2010)
In order to better aid in the development of integrated coastal management in the Westfjords, Iceland, a case study testing methods of juvenile fish sampling in shallow coastal areas and examining the effects of a bridge construction in Mjóifjörður on movement of gadoid fish were investigated during the fall months of 2009. Three different types of habitats: sand and gravel, maerl and kelp were sampled using gill nets as well as a baited camera system. Sampling took place in Mjóifjörður and in two of the surrounding un-impacted fjords. The abundance of juvenile Atlantic cod, Gadus morhua, as well as other gadoid fish and the by-catch were recorded from each method. Overall the results show a very low abundance of juvenile gadoids throughout the sampling area, and the previously un-tested baited camera system showed comparable results to the traditional sampling method of using gill nets in two of the three habitats investigated. Juvenile gadoid fish exhibited no differences in abundance between the fjords indicating no decrease in the movement of juveniles in the bridged fjord. Such information should aid in the decision making process regarding the management of such coastal engineering projects.